2011
DOI: 10.1002/adfm.201002361
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Separation Behavior of Hybrid Organosilica Membranes by Adjusting the Structure of the Organic Bridging Group

Abstract: Hybrid organically linked silica is a highly promising class of materials for the application in energy‐efficient molecular separation membranes. Its high stability allows operation under aggressive working conditions. Herein is reported the tailoring of the separation performance of these hybrid silica membranes by adjusting the size, flexibility, shape, and electronic structure of the organic bridging group. A single generic procedure is applied to synthesize nanoporous membranes from bridged silsesquioxane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(158 citation statements)
references
References 55 publications
6
146
0
Order By: Relevance
“…In DLCA, the approach of particles is governed by Brownian transport while the reaction rate is much higher than the rate of diffusion. A SAXS study on sols with -CH 2 -, -C 2 H 4 -, -C 8 H 16 -, -p-C 6 H 4 -and -p-C 6 H 4 -p-C 6 H 4 -bridging groups showed that although the reactivity of the precursors varied, the values of D i were similar (D i = 1.50-1.60) when the radii of gyration were similar (R g = 1.5-2.3 nm; hydrodynamic diameter 6 nm) [12]. Defect-free membranes with molecular sieving properties could be formed from all five sols.…”
Section: Sol Structure Evolution Monitored By In Situ Saxsmentioning
confidence: 81%
See 4 more Smart Citations
“…In DLCA, the approach of particles is governed by Brownian transport while the reaction rate is much higher than the rate of diffusion. A SAXS study on sols with -CH 2 -, -C 2 H 4 -, -C 8 H 16 -, -p-C 6 H 4 -and -p-C 6 H 4 -p-C 6 H 4 -bridging groups showed that although the reactivity of the precursors varied, the values of D i were similar (D i = 1.50-1.60) when the radii of gyration were similar (R g = 1.5-2.3 nm; hydrodynamic diameter 6 nm) [12]. Defect-free membranes with molecular sieving properties could be formed from all five sols.…”
Section: Sol Structure Evolution Monitored By In Situ Saxsmentioning
confidence: 81%
“…7 [13]. The permeability of water decreased gradually with increasing value of x. Aromatic bridges like p-phenylene and di-p-phenylene bridges (CH x :Si = 6, 12) seem to be less effective in promoting the flux of n-butanol compared with alkyl bridges with similar CH x :Si ratios [12].…”
Section: Pervaporationmentioning
confidence: 99%
See 3 more Smart Citations